Evaluasi pendidikan karakter disiplin siswa di SD Negeri 2 Gonilan - Cahyaningtyas, Arifah Yuni; Fatmasari, Erna Dwi; Annisa, Iut Diyah; Irta, Aisha; Ainur, Asri (Nur Science Institute, 2024)
The instillation of character education in schools, especially the character value of discipline, is carried out through daily activities in the school environment. This study aims to evaluate the achievement of the character education program at the elementary school level in Sukoharjo Regency and to provide input and suggestions to teachers and schools for improving the character program. This study is a program evaluation with a quantitative approach. The subjects of the study included fifth-grade students, homeroom teachers, teachers, security guards, and other parties directly involved with students in implementing activities related to character education. The data collection techniques used were interviews, questionnaires, and observations. The results of the study showed that the character education program of discipline at SD Negeri 2 Gonilan was running well and successfully. It is recommended that schools provide socialization to the community about the importance of character education of discipline and how to implement it at home so that students can implement the character of discipline not only at school but also at home in daily activities.